Pengaruh Costumer Bonding Terhadap Loyalitas Konsumen Pada Ilo Cake Pattiserie dan Bistro di Kota Bima - Mar’atin Amalia Rizkiah; Ismunandar Ismunandar; Ita Purnama (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2024)
This study aims to examine the influence of customer bonding on consumer loyalty in Ilo Cake Pattiserie and Bistro in Bima City. Customer bonding is defined as the process of building and maintaining a mutually beneficial relationship between a company and its customers. Consumer loyalty is measured by how often consumers return to buy products or services from a certain company. This study uses a quantitative method with a causal associative approach. A sample of 96 respondents was selected using the purposive sampling technique. Data was collected through the use of questionnaires with the Likert scale to measure respondents' perception of customer bonding and consumer loyalty variables. Data analysis was carried out using SPSS software to test validity, reliability, simple linear regression, correlation coefficient, determination coefficient, and t-test. The results of the study showed that there was a positive and significant influence between customer bonding on consumer loyalty at Ilo Cake Pattiserie and Bistro in Bima City (β = 0.545, p < 0.05). The coefficient of determination showed that 29.7% of the variation in consumer loyalty could be explained by the variable customer bonding. The implication of this study is the importance of an effective customer bonding strategy in maintaining consumer loyalty in the midst of fierce market competition. The conclusion of this study confirms that customer bonding plays an important role in increasing consumer loyalty. Recommendations for further research are to consider additional factors that can affect consumer loyalty as well as expand the scope of location and data analysis techniques to gain a deeper understanding.